2000
DOI: 10.1021/ma000191q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chiral Substituents on the Helical Conformation of Poly(propiolic esters)

Abstract: Propiolic esters having various chiral substituents, [HCtCCO2R*, R* ) (S)-(CH2)nCHMeEt (n ) 0-5), (1S,2R,5R)-isomenthyl, and (1S,2S,5S)-myrtanyl], were polymerized with [(nbd)RhCl]2 or MoOCl4-n-Bu4Sn for the purposes of establishing the relationship between the helical conformations of the polymers and the structures of pendant chiral groups. In contrast to the poor stereoregularities of the polymers prepared with MoOCl4-n-Bu4Sn, [(nbd)RhCl]2-catalyzed polymerizations resulted in polymers with high cis content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 15 publications
2
53
1
1
Order By: Relevance
“…89 Recently there are fairly many examples of helical substituted polyacetylenes; for example, induced helices based on the combinations of poly(p-carboxyphenylacetylene) and its analogues with low molecular weight compounds, 29,90 helical poly(p-alkoxy-m,m-dihydroxyphenylacetylene) synthesized by using chiral Rh catalyst systems, 28,91 and poly(menthyl/chiral alkyl propiolates). 92,93 The most salient feature of helical poly(Npropargylamides) developed by us is that the helix is mainly induced by the intramolecular hydrogen bonding between amide groups in the side chain.…”
Section: Helical Structurementioning
confidence: 99%
“…89 Recently there are fairly many examples of helical substituted polyacetylenes; for example, induced helices based on the combinations of poly(p-carboxyphenylacetylene) and its analogues with low molecular weight compounds, 29,90 helical poly(p-alkoxy-m,m-dihydroxyphenylacetylene) synthesized by using chiral Rh catalyst systems, 28,91 and poly(menthyl/chiral alkyl propiolates). 92,93 The most salient feature of helical poly(Npropargylamides) developed by us is that the helix is mainly induced by the intramolecular hydrogen bonding between amide groups in the side chain.…”
Section: Helical Structurementioning
confidence: 99%
“…[27,47] The polymerization of acetylene monomers having a chiral substituent can result in optically active MSPAs, owing to the formation of helical conformation with an excess screw sense. [11,13,18,24,[40][41][42][43]45,[48][49][50][51] A systematic study of the cis-transoidal PPAs bearing D-or L-alanine residues and with a long n-decyl chain as the pendants (Figure 2a) by Yashima and co-workers gives an excellent demonstration of the rigid rod-like MSPA with a predominant one-handed helical conformation. [52][53][54][55] On highly oriented pyrolytic graphite (HOPG), the chains losing their helical conformation are flat in the first monolayer, probably due to the strong and epitaxial adsorption of the long alkyl chains on the basal plane of graphite.…”
Section: Rod-like Mspas and Their Columnar Lc Phasesmentioning
confidence: 99%
“…[38][39][40][41][42][43] Percec et al have reported a library of dendronized polyphenylacetylene (PPA)s that exhibit chiral helical conformations both in solution and in solid (Fig. 1).…”
Section: Foldamers From Oligomers and Polymersmentioning
confidence: 99%